DEVELOPMENT OF PICTURE STORY BOOKS BASED ON DISCOVERY LEARNING ON ECONOMIC ACTIVITIES - Utomo, Eko Prasetyo (Soedirman Economics Education Journal, 2022)
This study aims to determine the process and results as well as the effectiveness of developing a picture story book based on Discovery Learning. The development model used is ADDIE (2009). The results of the product development of picture story books include: 1) the title of the book; 2) preface; 3) instructions for using the book; 3) story content; 4) activity sheet; 6) assessment; 7) bibliography and 7) glossary. The results of the validation test of material experts and learning media experts obtained an average score of 94.64% and 91.19% in the very feasible category. For the results of individual, small group, and field trials, respectively, the average scores were 89.32%, 90.95% and 93.08% and the category was very feasible. In the field trial, the results of the effectiveness test of the illustrated story book based on Discovey Learning showed that the product developed was effective in improving students' cognitive learning outcomes on economic activities.